Bìsíwéérí: songs of a Muslim Chamba woman (Gongola State, Nigeria) - (:unkn) unknown (My University, 1992)
This paper presents a number of songs composed and sung by a Nigerian woman belonging to the Chamba Daka (Sámá) ethnic group. They were originally recorded by the singer's son, who provided explanations in addition to the singer's own comments. The lyrics are interpreted and placed in their historical context. The conclusion summarily places the musical and lyrical features in a wider African context.
Keywords: African Research